Kompetensi Sosial Kepala Madrasah Dalam Memberdayakan Komite Untuk Peningkatan Sarana Prasarana di MAN 1 Tulungagung - Eko Sulistiyanto; Nur Efendi; Sulistyorini (STAI Terpadu Yogyakarta, 2023)
The research is aimed at describing and analyzing the social competence of madrasa heads in empowering school committees to improve madrasa facilities and infrastructure. This research uses a qualitative research approach with a case study type of research. The data in this research was collected using interview, observation and documentation techniques, while the data analysis technique used was data triangulation techniques. The results of the research show that the social competence that must be possessed by madrasah heads concerns several things, including: a) collaborating with other parties for the benefit of the Madrasah; b) participate in social activities; c) have social sensitivity towards other individuals or groups. By empowering committees to improve madrasa facilities and infrastructure, madrasas can utilize additional resources, gain community support, manage projects more efficiently, and build sustainable capacity.